2016
DOI: 10.1088/0741-3335/58/4/045004
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of ion and electron heat transport of high-TeECH heated discharges in the large helical device

Abstract: An analysis of the radial electric field and heat transport, both for ions and electrons, is presented for a high-T e electron cyclotron heated (ECH) discharge on the Large Helical Device (LHD). Transport analysis is done using the task3d transport suite 1 utilizing experimentally measured profiles for both ions and electrons. Ion temperature and perpendicular flow profiles are measured using the recently installed x-ray imaging crystal spectrometer diagnostic (XICS) 2 , while electron temperature and density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…The electron heat diffusivity is also at the ion neoclassical heat diffusion level, but remains significantly above the electron neoclassical heat diffusivity, consistent with observations at JT-60U [10]. Similarly, a transport analysis of a high-T e electron cyclotron heated plasma in LHD showed that while the measured electron heat flux exceeds the neoclassical values by an order of magnitude, the measured ion heat flux is comparable to the neoclassical prediction [11].…”
Section: Nuclear Fusionsupporting
confidence: 83%
“…The electron heat diffusivity is also at the ion neoclassical heat diffusion level, but remains significantly above the electron neoclassical heat diffusivity, consistent with observations at JT-60U [10]. Similarly, a transport analysis of a high-T e electron cyclotron heated plasma in LHD showed that while the measured electron heat flux exceeds the neoclassical values by an order of magnitude, the measured ion heat flux is comparable to the neoclassical prediction [11].…”
Section: Nuclear Fusionsupporting
confidence: 83%
“…Using standard Doppler spectroscopy techniques, this diagnostic can provide line-integrated profiles of the ion-temperature (T i ) from line broadening, electron temperature (T e ) from line ratios, perpendicular flow velocity (u ⊥ ) from line shifts and impurity concentration from the line brightness. Tomographic inversion, using a known plasma equilibrium is used to infer the local plasma parameters from the line integrated data 8,9 . A description of the XICS system on W7-X can be found in Ref.…”
Section: Diagnostic Methodsmentioning
confidence: 99%
“…Radial electric fields and the comparison between NC theory and experiments have been studied on other many other stellarator devices [9,10] including LHD [11,12], W7-AS [13,14], TJ-II [15], HSX [16,17], CHS [18,19] and Heliotron-J [20]. The experimental uncertainties and level of quantitative agreement varies between these studies, however overall they all point towards the validity of neoclassical theory in describing the ambipolar radial electric field.…”
Section: Introductionmentioning
confidence: 99%